Does Procyclical Fiscal Policy Reinforce Incentives to Dollarize Sovereign Debt? - Ilyina, Anna (IMF Working Papers; Working Paper, 2010)
This paper explores the link between the cyclical patterns of macroeconomic and policy variables and the currency composition of domestic sovereign debt in emerging market countries. The empirical analysis is anchored in an equilibrium model, in which the dollarization of sovereign debt arises as a result of the optimal portfolio choices by risk-averse investors, and of a sovereign debt manager who takes fiscal policy as given. The model predicts that in countries where the exchange rate is countercyclical (i.e., the exchange rate depreciates during recessions), a more procyclical fiscal policy (i.e., expansionary in good times and contractionary in bad times) would lead, on average, to a more dollarized domestic sovereign debt. The empirical analysis using the Jeanne-Guscina EM Debt database (2006) on the currency structure of the central government debt in 22 emerging market countries over 1980 - 2005, supports these predictions.